2017
DOI: 10.18488/journal.1.2017.79.738.753
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Violence Beliefs and Stereotypes: Cross-Cultural Comparison Across Three

Abstract: Article HistoryCultural values, beliefs, and stereotypes have significant effects on violence against women across societies but knowledge about gender-based violence beliefs and stereotypes across societies is sparse. Using multiple theoretical perspectives (e.g., feminist theory, varieties of patriarchy, social dominance theory, and ambivalent sexism) and human development and the Gender Inequality Index, this study examined beliefs about relationship violence against women and gender beliefs and stereotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…In contrast, perpetrators tend to be male, and this trend becomes more evident as the severity of sexually violent crimes increases (Longpré et al, 2018). The higher endorsement of Rape Myths and worse perception of harassment observed in men support past findings from Fakunmoju and Bammeke (2017) and Cortina and Berdahl (2008) respectively. Gender was one of the best predictors of harassment and, for Rape Myths, it was even a slightly better predictor than everyday sadism.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, perpetrators tend to be male, and this trend becomes more evident as the severity of sexually violent crimes increases (Longpré et al, 2018). The higher endorsement of Rape Myths and worse perception of harassment observed in men support past findings from Fakunmoju and Bammeke (2017) and Cortina and Berdahl (2008) respectively. Gender was one of the best predictors of harassment and, for Rape Myths, it was even a slightly better predictor than everyday sadism.…”
Section: Discussionsupporting
confidence: 88%
“…The findings that adolescents from Nigeria were more likely to be exposed to both IPV and family violence than adolescents from South Africa provide a unique opportunity to understand cross-national differences in experience among adolescents in the two countries, especially given the lack of comparative knowledge about these differences. Although comparative knowledge about adolescents is minimal, the finding that adolescents from Nigeria were more likely to endorse beliefs about VAW than adolescents from South Africa is consistent with previous studies that found adult respondents in Nigeria to be more likely to endorse VAW and gender stereotypes than respondents in South Africa (Fakunmoju & Bammeke, 2017;Fakunmoju et al, 2016). Altogether, these findings can be explained by some macro-level differences between the two countries as discussed below.…”
Section: Effects Of Gender and Country On Exposure To Ipv Exposure Tsupporting
confidence: 88%
“…GBV is a social ill evident across all the countries irrespective of their economy, language, and demography. However, with country, the type of GBV, its intensity, and the reaction of people vary ( Fakunmoju, Bammeke et al, 2017 ). For example, in the USA, dating violence is more common than in Africa where there are comparatively lesser instances of dating violence ( Johnson et al, 2015 ).…”
Section: Related Workmentioning
confidence: 99%